Organizational Documents Exercise - Roy, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Find a document or cultural artifact created by a non-governmental organization for an organizational purpose (that is, its content should not be incidental to how the organization operates, as say, a book would be for publisher), created in some or place other than twenty-first century US. It can be from a publication, an archive, the web, or personal collection. It can be intended either for public consumption (for example, an annual report), or internal consumption.